Affirmative action, diversity, and racial justice: Reflections from a diverse, non-elite university. (November 2016) - Blum, Lawrence
In this article, I argue (1) affirmative action diverts attention from more urgent needs of racial justice in education – better quality K-12 education, and better quality and more accessible public higher education; (2) the increasing wealth of students at affirmative action institutions is a sign of diminished quality of those students compared to those at less selective institutions, who are comparatively disproportionately black and Latino; and (3) aligning the standard rankings of colleges with the quality of student (and quality of instruction at the different kinds of institution) would benefit black and Latino students as a group much more than affirmative action does.